Socialisation, Trust and Reciprocity among Young People - Matteo Migheli (Swiss Journal of Economics and Statistics, 2012)
This paper analyzes the contribution of youth's different time allocations to positive behaviours in exchanges. Psychologists highlight that time spent within voluntary organizations fosters positive development. The paper aims at deepening the knowledge of the psychological bases of the observed outcomes of a basic trust game. Undergraduate students played a basic trust game; after this, information about the use of their spare time was collected. Higher passed amounts positively correlate with time spent in youth organizations. The main novelties of the paper are: the way social capital is measured and the strong link with the psychological literature.
Keywords: C93; D01; Z13; 330; trust; reciprocity; social capital